Дослідження в Ніжині та Новгороді-Сіверському в 2009 р. - Кедун, І.С. (Археологічні дослідження в Україні, 2010)
Information is presented about the 2009 excavations on the territory of cities in Chernihiv-Siverskyi region mentioned in chronicles: Nizhyn (Unenezh) and Novhorod-Siverskyi.